2020
DOI: 10.21082/jlittri.v26n2.2020.78-91
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY OF EXTRACELLULAR ENZYMES PRODUCED BY ENDOPHYTIC FUNGUS ORIGINATED FROM Centella asiatica (L.) Urban

Abstract: Tanaman Pegagan (Centella asiatica) adalah tanaman obat yang dikenal bersimbiosis dengan berbagai jenis jamur endofit. Jamur endofit dipelajari secara ekstensif sebagai sumber senyawa bioaktif baru, termasuk enzim ekstraseluler. Enzim asparaginase, amilase, selulase, pektinase, protease, glukanase, dan lakase digunakan dalam industri. Penelitian ini bertujuan untuk mengkarakterisasi beberapa produksi enzim dari 40 jamur endofit dari C. asiatica. Penelitian dilakukan di Laboratorium Mikrobiologi, Balai Besar Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous researches have identified several bioactivities, such as extracellular enzymes (asparaginase, amylase, cellulase, pectin, protease, glucanase, laccase) producer, antimicrobial, and antioxidant activity produced by endophytic fungi from Asiatic pennyworth (Susilowati et al 2020). It has been found that the endophytes produce a significant amount of antioxidants, which prevent oxidative damage to cellular components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have identified several bioactivities, such as extracellular enzymes (asparaginase, amylase, cellulase, pectin, protease, glucanase, laccase) producer, antimicrobial, and antioxidant activity produced by endophytic fungi from Asiatic pennyworth (Susilowati et al 2020). It has been found that the endophytes produce a significant amount of antioxidants, which prevent oxidative damage to cellular components.…”
Section: Introductionmentioning
confidence: 99%